A few good (wo)men? Gender diversity on Australian boards. (August 2017) - Strydom, Maria; Au Yong, Hue Hwa; Rankin, Michaela
This article examines the relation between gender diversity and earnings quality for Australian firms from 2005 to 2013. We draw on the work of Kanter, highlighting the importance of the proportion of women on the board when measuring diversity. We show that all-male and skewed boards have lower earnings quality while that of tilted and balanced boards is higher. In addition, a critical mass of women is achieved when some 30% of directors are females. Performance and risk do not influence the relation. We contribute by presenting evidence supporting critical mass theory. Furthermore, our work adds to the recent debate on whether the association between gender diversity and earnings quality is U-shaped, rather than linear. Our results have implications for regulation and practice. We identify the need for a critical mass of women, rather than tokens, to enhance earnings quality.